2001
DOI: 10.1354/vp.38-6-679
|View full text |Cite
|
Sign up to set email alerts
|

Point Mutation of neu Oncogene in Animal Peripheral Nerve Sheath Tumors

Abstract: Abstract. Thirty-four peripheral nerve sheath tumors of four domesticated animal species were characterized and assayed for point mutation of the neu oncogene. Based on their morphoimmunophenotype, 32 tumors were classified as schwannomas. Schwannoma morphology was characterized by the presence of Antoni type A and B pattern and immunoreactivity for S-100 protein and vimentin. Two anaplastic and metastatic tumors originating from spinal cord root, immunonegative for S-100 protein and positive for vimentin, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
0
15

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(92 citation statements)
references
References 14 publications
7
70
0
15
Order By: Relevance
“…Also, in our study, all cases showed a consistently expression of vimentin. Previous investigations reported that, in veterinary medicine, vimentin is an immunohistochemistry marker invariably positive in all PNSTs regardless its biological behavior (5,11,13,16,19,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Interestingly, in our study, differences in the labeling intensity were observed between the benign and the malignant cases that beared on the decreased of the vimentin score values within the latter group.…”
Section: Discussionsupporting
confidence: 54%
“…Also, in our study, all cases showed a consistently expression of vimentin. Previous investigations reported that, in veterinary medicine, vimentin is an immunohistochemistry marker invariably positive in all PNSTs regardless its biological behavior (5,11,13,16,19,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Interestingly, in our study, differences in the labeling intensity were observed between the benign and the malignant cases that beared on the decreased of the vimentin score values within the latter group.…”
Section: Discussionsupporting
confidence: 54%
“…A manifestação neurológica em todos os membros foi determinada pelo acometimento da medula espinhal cervical, que apresentou à histologia infiltração da neoplasia, com destruição de parte da substância branca, caracterizada por degeneração axonal e necrose neuronal (Simpson et al, 1999). As áreas de aspecto mixomatoso e os focos de metaplasia cartilaginosa observadas à histologia do caso 1 já foram descritas por Summers et al (1995) em uma revisão da morfologia desses tumores relatando diferenciação ostóide, condróide, mixóide e padrão escamoso. Os achados anatomopatológicos foram essenciais para se estabelecer o diagnóstico de tumor da bainha do plexo braquial, pois dificilmente esse tipo de tumor pode ser diagnosticado apenas com base nos achados clínicos (Simpson et al, 1999).…”
Section: Discussionunclassified
“…Esse marcador é específico para tipo celular de origem neural (Patnaik et al, 2002;Garcia et al, 2004), semelhante ao que ocorre no homem, no qual 50 a 90% dos tumores malignos de bainha nervosa apresentam positividade para proteína S-100 (Sawamoto et al, 1999). Entretanto, estudo realizado por Stoica et al (2001) demonstrou que imunoistologicamente tumores malignos de bainha nervosa podem ser negativos para proteína S-100 e positivos para vimentina, o que também foi observado no animal do caso 3 descrito neste trabalho (Fig. 1D).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Nos TBNP caninos, a presença do clássico padrão histológico Antoni A e Antoni B não é predominante como nos tumores humanos (STOICA; TASCA; KIM, 2001). Os TMBNP apresentam acentuado pleomorfismo, alta celularidade, necrose, hemorragia, elevado índice mitótico, comportamento invasivo e podem desenvolver metástase em órgãos distantes.…”
Section: Relato De Casounclassified